BDNF Val66Met Polymorphism Reduces the Fatigue-Like Effects of 5-Fluorouracil on Voluntary Wheel-Running Activity in Mice - Wolff, Brian S.; Allen, Hannah R.; Feng, Li Rebekah; Saligan, Leorey N. (Frontiers in Behavioral Neuroscience, 2022)
Fatigue is a persistent and debilitating symptom following cancer treatments such as chemotherapy. Recent clinical studies have suggested a common single-nucleotide polymorphism of brain-derived neurotrophic factor (BDNF), Val66Met (rs6265), may be related to the severity of fatigue following cancer treatment. In this study, we tested transgenic mice expressing the human Val66Met BDNF gene and wild-type controls. We injected three doses of 5-fluorouracil (5FU) as a model of chemotherapy treatment, and we used changes in voluntary wheel running activity as a measure of fatigue-like behavior. Prior to 5FU injection, we found that during the baseline wheel-running period, the Val66Met mice lost more weight than WT controls. We next administered 5FU and saw a robust fatigue-like phenotype that lasted about two weeks. During the first week, the fatigue-like phenotype was less severe in the Val66Met mice and unrelated to the age of the mice. In contrast, during the second week after 5FU treatment, the fatigue-like phenotype was unrelated to the BDNF genotype and was instead more severe in older mice. We conclude that the BDNF polymorphism may play a direct, protective role against chemotherapy-induced fatigue.